Genetic analysis of neuroendocrine tumor cells in prostatic carcinoma - Sauer, Christian; Römer, Alexandra; Grobholz, Rainer (The prostate, 2006)
BACKGROUND Neuroendocrine differentiated tumor cells can be found in the majority of prostatic adenocarcinomas. During antiandrogen or androgen-withdrawal therapy the neuroendocrine differentiation is often increased but its prognostic value is discussed controversially. The origin of neuroendocrine tumor cells is under discussion. While double staining experiments suggest a non-neoplastic pluripotent stem cell, in vitro studies demonstrate a transdifferentiation of exocrine tumor cells to a neuroendocrine phenotype. METHODS Neuroendocrine differentiated LNCaP cells and laser captured microdissected cells of eight radical prostatectomies were allelotyped using 11 microsatellite markers from seven different loci. RESULTS Identical allelic profiles were detected in untreated and neuroendocrine differentiated LNCaP cells for all markers confirming their clonality. Neuroendocrine and exocrine tumor cells from radical prostatectomies shared identical allelic profiles for all markers, suggesting a common origin for both cell populations. CONCLUSIONS Our results support the concept of transdifferentiation of exocrine tumor cells to a neuroendocrine tumor cell phenotype. © 2005 Wiley-Liss, Inc.
First published: 19 September 2005
Gesehen am 31.05.2022